Zirconium tetraazamacrocycle complexes display extraordinary stability and provide a new strategy for zirconium-89-based radiopharmaceutical development12. Issue 3 (20th December 2016) - Pandya, Darpan N.; Bhatt, Nikunj; Yuan, Hong; Day, Cynthia S.; Ehrmann, Brandie M.; Wright, Marcus; Bierbach, Ulrich; Wadas, Thaddeus J.
Abstract : 89 Zr–Tetraazamacrocycle complexes display extraordinary stability. Abstract : We report our initial investigations into the use of tetraazamacrocycles as zirconium-89 chelators. We describe the synthesis and complete characterization of several Zr tetraazamacrocycle complexes, and definitively describe the first crystal structure of zirconium 1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid (Zr–DOTA) using single crystal X-ray diffraction analysis. After evaluating several radioactive analogs, we found that 89 Zr–DOTA is superior to 89 Zr–DFO, the only 89 Zr-complex to be used clinically in 89 Zr-radiopharmaceutical applications. Finally, we provide a rationale for the unanticipated and extraordinary stability of these complexes in vitro and in vivo . These results may inform the development of safer and more robust immuno-PET agents for precision medicine applications.